THE FUNCTION CHANGE OF POTEHI PUPPET PERFORMANCE IN CHINESE TRADITION IN JAKARTA - Stephany Maria Tahalele (Bambuti, 2021)
This paper shows the development of wayang potent in Jakarta, changes in its function, the causes of changes in the function of wayang potent performances in Jakarta, and the impact of changes in the function of wayang potent performances for Chinese culture and society. In this writing, the research used is a qualitative method based on literature study, observation, and interviews. Based on this paper, it can be concluded that the wayang’s potent performance in its development has changed function and its performance has begun to adapt to the local culture. Currently, wayang potehi is not only performed at the temple but has begun to spread to the stage for entertainment outside the temple.